Improved design of sliding mode control for civil structures with saturation problem. - Lee, Sang-Hyun
A systematic and improved design procedure for sliding mode control (SMC) of seismically excited civil structures with saturation problem is provided in this paper. In order to restrict the control force to a certain level, a procedure for determining the upper limits of the control forces for single or multiple control units is proposed based on the design response spectrum of external loads. Further, an efficient procedure using the LQR method for determining sliding surfaces appropriate for different controller types is provided through the parametric evaluation of the dynamic characteristics of sliding surfaces in terms of SMC controller performance. Finally, a systematic design procedure for SMC required to achieve a given performance level is provided and its effectiveness is verified by applying it to multi-degree of freedom (MDOF) systems.
Keywords: Controller design; Saturation problem; Sliding mode control